Online Food Delivery Services: Make or Break the Halal Supply Chain? - Nina Naquiah Ahmad Nizar; Siti Aimi Sarah Zainal Abidin (Journal of Food and Pharmaceutical Sciences, 2021)
Online food delivery service (FDS) is the new gig economy in this era of new normal. Online FDS refers to the process whereby food that was ordered online is prepared and delivered to the consumer. FDS falls at the end of a food supply chain, the final stage just before the food reaches customers. However, this stage can make or break a wholesome food production, particularly in halal food supply chain. This paper revisits the guidelines of FDS in Malaysia; then extended to the measures taken during Covid-19 pandemic. The focus is food safety and quality, and halal supply chain. It is hoped that this overview will become a source of information for the public for their peace of mind, and the food delivery service providers to deliver wholesome food to their customers